Effect Of Tetramethylammonium Hydroxide (TMAH) Etchant On The Formation Of Silicon Nanowires Transistor Patterned By Atomic Force Microscopy (AFM) Lithography - Lew, Kam Chung (2011)
In this research, AFM lithography was performed to create nanoscale oxide pattern of silicon nanowires transistor (SiNWT) structure via local anodic oxidation (LAO) process on silicon on insulator (SOI) surface. These nanoscale oxide patterns will act as a mask to protect silicon layer during etching. The SiNWT structures consist of a nanowire as a channel with contact pads of source (S), drain (D) and lateral gate (G). The fabricated device structure was then wet chemically etched with tetramethylammonium hydroxide (TMAH) and hydrofluoric acid (HF) to remove the uncover silicon layer and oxide layer, respectively.